HUBUNGAN SOSIODEMOGRAFI, STATUS INDEKS MASSA TUBUH, DAN TINGKAT AKTIVITAS FISIK DENGAN KEBUGARAN JASMANI PADA PEGAWAI (Studi Pada Pegawai Aparatur Sipil Negara (ASN) di Kabupaten Semarang) - Indah Nisrina Sarahfatin; Ari Udijono; Sri Yuliawati; Henry Setyawan Susanto (Jurnal Kesehatan Masyarakat (Undip), 2021)
Physical fitness is the main capital needed for one's work productivity, especially for employees of the state civil servants (ASN). Judging from the number of ASN jobs carried out every day, good work productivity is needed in serving the needs of the community. This study aims to analyze the relationship between sociodemography, body mass index status and level of physical activity with physical fitness for ASN employees in Semarang Regency. This research was conducted using quantitative observational research methods with cross sectional approach. The sample in this study were 82 respondents using the total sampling technique. This study used a questionnaire containing questions about the characteristics of the respondents, level of physical activity and frequency of physical exercise. This study used univariate and bivariate analysis and the results showed a significant relationship between age (p-value = 0.006), gender (p-value = 0.025), body mass index status (p-value < 0.001), level of activity. physical training (p-value < 0.001) and frequency of physical exercise (p-value < 0.001) with physical fitness for ASN employees.